Intimate Partner Violence as Reflected in Internet Search Data - Youngmann, Brit; Yom-Tov, Elad (Social Science Computer Review, 2022)
Intimate partner violence (IPV) is a major public health concern with serious consequences for victims’ physical and mental health. Despite the high prevalence of IPV, describing it and detecting people suffering from it is difficult due to its sensitive nature and stigma associated with it. Existing tools for screening and tracking IPV victims are laborious, time-consuming, expensive, and require human supervision. Search engine data has previously been shown to provide insights into temporal behavioral information about millions of users who are truthful in their information seeking. Here, we present a large-scale analysis of individuals experiencing IPV providing insights into their characteristics and behavior. We extracted the queries from Bing search engine data of more than 50 thousand US-based individuals suffering from IPV. We provide insights into the differences among subpopulations of people experiencing IPV and the topics they search for. We find that approximately half of the users begin to search for IPV following an acute event (physical violence or abuse) and 20% of users actively hide their interest in IPV. Users typically begin to seek help 3 weeks after beginning to query about IPV. The topics of interest to people experience IPV include the effects of IPV, help seeking, and methods to escape from IPV. Our insights show that early cues of IPV may be difficult to detect within search queries, though even in the late stage that many IPV users are identified, interventions such as ads to guide people to safely exit violent situations could be beneficial.